1983
DOI: 10.1079/bjn19830007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pharmacological doses of ascorbic acid on the hepatic microsomal haemoproteins in the guinea-pig

Abstract: 1. Ascorbic acid deficiency results in a reduction in the activity of the hepatic mixed function oxidase systems in the guinea-pig. In this study, male Dunkin-Hartley guinea-pigs were given 0, 50, 100, 200 or 300 mg ascorbic acid/d in two equal doses in buffered sucrose solution (200 g/l) for 4 d. Controls received an equal volume of sucrose solution.2. A dose of 50 mg ascorbic acid/d resulted in a significant rise in the specific activities of both cytochromes P-450 and b,. At doses of 200 and 300mg ascorbic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…No change in blood parameters including serum albumin, globulin, albumin/globulin ratio, total bilirubin, alkaline phosphatase, alanine aminotransferase, aspartate aminotransperase, r-glutamyltransferase and lactate dehydrogenase contents suggests that feeding dry or fermented diets did not cause any abnormal liver functions in the rats. Serum uric acid levels in humans can be affected by dietary factors such as Zn (Umeki et al, 1986) and ascorbic acid (Sutton et al, 1983). In a study with rats increased levels of serum uric acid was shown to be associated with high blood pressure and renal disease (Mazzali et al, 2001).…”
Section: Blood Parametersmentioning
confidence: 99%
“…No change in blood parameters including serum albumin, globulin, albumin/globulin ratio, total bilirubin, alkaline phosphatase, alanine aminotransferase, aspartate aminotransperase, r-glutamyltransferase and lactate dehydrogenase contents suggests that feeding dry or fermented diets did not cause any abnormal liver functions in the rats. Serum uric acid levels in humans can be affected by dietary factors such as Zn (Umeki et al, 1986) and ascorbic acid (Sutton et al, 1983). In a study with rats increased levels of serum uric acid was shown to be associated with high blood pressure and renal disease (Mazzali et al, 2001).…”
Section: Blood Parametersmentioning
confidence: 99%
“…Reports suggest antioxidant supplements, including vitamin C and E, reduce both oxidative stress and serum uric acid levels [ 56 ]. Choi et al reported that taking 1.5 g of vitamin C daily is associated with a 45% reduced incidence of gout [ 57 ]; consuming 3.0 g/day resulted in transient increases in uric acid excretion in one study [ 58 ] and a 102% increase in uricosuria in another [ 59 ]. These findings that vitamin C promotes uricosuria have led to speculation that uric acid and vitamin C compete with each other for reabsorption [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…and 3) Investigation of the thiamin antagonistic effect of widely used cytotoxic agent 5-fluorouraci on malignant diseases [45][46][47]. Dr. Basu's research on various aspects of ascorbic acid is well known, in particular, his extensive reports against its Mega dose usage have been considered to be fundamental and have received much attention [39,44,[48][49][50]. Dr. Basu's recent research investigation on diabetes is another major break through in the contemporary nutritional research realm.…”
Section: Dr T K Basu's Research Profile and Our Common Research Inmentioning
confidence: 99%